Higher derivative Chern-Simons extension in the noncommutative QED3 - Ghasemkhani, M.; Bufalo, R. [UNESP] (American Physical Society (APS), 2015)
The noncommutative (NC) massive quantum electrodynamics in 2+1 dimensions is considered. We show explicitly that the one-loop effective action arising from integrating out the fermionic fields leads to the ordinary NC Chern-Simons and NC Maxwell action at the long wavelength limit (large fermion mass). In the next to leading order, the higher-derivative contributions to NC Chern-Simons are obtained. Moreover, the gauge invariance of the outcome action is carefully discussed. We then consider the higher-derivative modification into the pure NC Chern-Simons Lagrangian density and evaluate the one-loop correction to the pole of the photon propagator.